2001
DOI: 10.1108/01409170110782432
|View full text |Cite
|
Sign up to set email alerts
|

Strategic planning process in developing countries: the case of United Arab Emirates business firms

Abstract: Attempts to shed light on some of the leading works in the field of strategic planning. Presents the findings from research into the existence of strategic planning in United Arab Emirates business firms, asking whether any planning has relationships with feature or characteristics of the business and finding out who is involved in the process. Suggests that the prevalence is low and not seen as beneficial. Proffers some suggestions which may explain why this may be the case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
0
21
0
3
Order By: Relevance
“…There are three possible explanations of this result. First, though most organizations, in the UAE nowadays have strategic plans and the managers of these organizations have very positive attitudes toward strategic planning, most of the UAE's organizations are new since the UAE itself is a new state, and strategic planning is still a recent practice in its organizations (Al‐Shaikh, 2001; Elbanna, 2010). This may be an indication that managers of organizations in the UAE, compared to their counterparts in developed countries, still need more time to improve the strategic planning process and recognize the actual impact of extensive strategic planning on performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three possible explanations of this result. First, though most organizations, in the UAE nowadays have strategic plans and the managers of these organizations have very positive attitudes toward strategic planning, most of the UAE's organizations are new since the UAE itself is a new state, and strategic planning is still a recent practice in its organizations (Al‐Shaikh, 2001; Elbanna, 2010). This may be an indication that managers of organizations in the UAE, compared to their counterparts in developed countries, still need more time to improve the strategic planning process and recognize the actual impact of extensive strategic planning on performance.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this century, the prevalence of strategic planning in the UAE was low and organizations seemed not to take strategic planning seriously or practise it properly (Al‐Shaikh, 2001). During the last decade, major changes have taken place in the UAE regarding the practice of strategic planning; and in consequence it has recently been reported that managers in the UAE organizations have very positive attitudes toward strategic planning, more than 80 per cent of organizations have written strategic plans and they appear to have adopted a structured approach to strategic planning (Elbanna, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to Al-Shaikh (2001), the UAE has a multicultural business environment. The workforce in the country comes from almost every corner of the world.…”
Section: Health Care In the Uaementioning
confidence: 99%
“…Despite more than four decades of research, the question of whether strategic planning has an impact on organizational performance remains unresolved (Al‐Shaikh, ; Al‐Shammari & Hussein, ). Various researchers have attributed inconclusive findings on the issue to methodological shortcomings, such as most studies being too focused on the direct effects of strategic planning on performance, inconsistencies in the operationalization of strategic planning, and studies being limited to financial measures (e.g., Greenley, ; Phillips & Moutinho, ; Rudd, Greenley, Beatson, & Lings, ).…”
Section: Introductionmentioning
confidence: 99%
“…One might think that the UAE may not be a proper setting to conduct a study on strategic planning as it represents an economy where competition is not intense and firms are small and family‐owned, making the relevance of strategic planning questionable (Al‐Shaikh, ). While early research on strategic planning in the UAE (e.g., Al‐Shaikh, ) suggests that this assumption is not without merits, more recent studies reveal that many UAE firms engage in strategic planning and take it seriously (Yusuf & Saffu, ) and, irrespective of their being a public, private, small, or large firm, they have a strongly supportive attitude toward strategic planning (Elbanna, ; see also Elbanna, , ; Siddique, ).…”
Section: Introductionmentioning
confidence: 99%